To evaluate an equation for specific values of \( x \), you need to substitute those values into the equation and then perform the calculations.
Let's say we have a general equation \( f(x) \). For demonstration, I'll use a simple equation like \( f(x) = x^2 + 3x + 1 \).
Step 1: Plug in \( x = 2 \)
-
Substitute \( x = 2 \) into the equation: \[ f(2) = (2)^2 + 3(2) + 1 \]
-
Calculate: \[ f(2) = 4 + 6 + 1 = 11 \]
Step 2: Plug in \( x = 6 \)
-
Substitute \( x = 6 \) into the equation: \[ f(6) = (6)^2 + 3(6) + 1 \]
-
Calculate: \[ f(6) = 36 + 18 + 1 = 55 \]
Summary of the results:
- For \( x = 2 \), \( f(2) = 11 \)
- For \( x = 6 \), \( f(6) = 55 \)
You can replace \( f(x) = x^2 + 3x + 1 \) with any other equation, just follow the same substitution and evaluation steps.